A systematic review and meta-analysis of the role of doxycycline in chronic rhinosinusitis. Issue 5 (3rd May 2023) - Chan, D; Ooi, E; Khalid, O
Abstract: Objective: The objective of this systematic review and meta-analysis was to evaluate the role of doxycycline in the management of chronic rhinosinusitis. Method: This was a systematic review using Ovid Medline, Cinahl, Scopus and Cochrane and was limited to meta-analyses, systematic reviews and randomised, clinical trials. A combination of the following search terms was used: 'sinusitis', 'nasal polyps', 'doxycycline' and 'tetracycline'. Raw means and standard deviations were extracted from the included studies. The meta-analysis was performed using mean differences of pre- versus post-doxycycline treatment. Results: A total of 279 studies were screened, of which 5 studies met the criteria (all randomised, controlled trials published between 2010 and 2021). The interventions, endpoints and measured outcomes varied across all studies. Meta-analysis performed on pre- versus post-doxycycline treatment for Sino-Nasal Outcome Test-22, nasal polyp scores and symptom scores did not yield statistically significant results. Conclusion: This review identified a small number of high-quality studies on the use of doxycycline in chronic rhinosinusitis. There does not seem to be convincing evidence for the routine use of doxycycline in patients with chronic rhinosinusitis. Further research may try to identify certain phenotypes of chronic rhinosinusitis that may better respond to doxycycline.